Phonics Reading Strategy: An Alternative Strategy to Improve EYL Students’ Reading Skill - Fitri Arniati; Sri Ningsih; Devianti Devianti; Arma Amir Hamzah (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
The introduction of English to young learners has been implemented for a long time with various strategies and approaches. However, not all of strategies the teacher used were successful in being applied in the classroom. Based on pre-observation, the students’ reading interest is low due to difficulty understanding the text. They have difficulty understanding sentences, and students can only find the meaning of the sentence or only understand the text content's outline. The present study aims to determine whether reading phonics strategy can improve students reading skill in second-grade of SMP Negeri 2 Sumarorong. The study used a pre-experimental method in one class given a pre-test and a final test. The population is the second-grade students and this study used a total sampling technique. The result of the data shows that the mean value in the final test is greater than the mean value of the initial test (79.52>60.800), and the t-test value is greater than the t-table value (12.046>2.046) at the level of increase of 0.05, with degrees of freedom (df) 24. This increase can also be seen from the post-test result, which is greater than the pre-test score. This evidence highlighted phonics reading strategy can improve students reading skill.